Pengaruh Influencer Marketing, Content Marketing dan Online Customer Review Terhadap Keputusan Pembelian Produk PVN SHOES (Studi Kasus pada Mahasiswa di Kota Malang) - Susanti, Diva Dwi; Sudaryanti, Dwiyani; Efendi, Erfan (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to analyze how the influence of the Influencer Marketing, Content Marketing, and Online Customer Review on purchase decisions of PVN Shoes items in Malang City. The method used is quantitative with sampling techniques based on the Malhotra formula, resulting in 90 respondents. Data analysis used is multiple linear regression with SPSS 26 analysis tools, complemented by partial (t test) and simultaneously (F test) hypothesis testing. The result showed that the three had a significant effect both partially and simultaneously on purchase decisions. The findings of this research indicate that the importance of digital marketing strategies in the form of Influencer Marketing, Content Marketing and Online Customer Review in improving consumer purchasing decisions. Keywords: Influencer Marketing, Content Marketing, Online Customer Review and Purchase Decisions